Whither Formal Contracts? - Sánchez de la Sierra, Raúl (Econometrica, 2021)
To measure the benefits of formal contract enforcement for society, I create a market with merchants and buyers, in which buyers can choose whether to buy, and whether to pay. A set of multiple “state‐favored” ethnic groups control the state. I experimentally vary whether formal contracts are required and the composition of buyer‐merchant pairs. The design separately identifies the effect of the contracts on the buyers' incentive to pay and on their incentive to buy. I document two ways in which society limits the benefits of contracts. First, contracts reduce buyer cheating, thus increasing merchants' profits, if, and only if, the merchant is state‐favored. Buyers' beliefs suggest that the merchants can enforce the contracts if, and only if, the merchant is state‐favored. Second, holding constant whether the pair is state‐favored, contracts only influence buyer choices when the buyer and the merchant belong to two, different, state‐favored ethnic groups. Buyers' choices and beliefs confirm that, in that case, the contracts are expected to be enforceable, but they have no effect on buyers' choices because reputation already governs the incentives to cheat within groups. The findings temper the view of the state as independent from society, offer a rationale for why contracts are not adopted, and nuance the notion of state weakness.